Teaching multiparadigm programming based on object-oriented experiences - Porkoláb, Zoltán; Zsók, Viktória (Teaching Mathematics and Computer Science, 2007)
Multiparadigm programming is an emerging practice in computer technology. Co-existence of object-oriented, generic and functional techniques can better handle variability of projects. The present paper gives an overview of teaching multiparadigm programming approach through typical language concepts, tools in higher education. Students learning multiparadigm-oriented subjects would gain considerable expertise, which is highly needed by the industrial side in large-scale application development.